Analysis of Sema No. 2/2023 on Interfaith Marriage Registration Under UU Adminduk Analisis Sema Nomor 2 tahun 2023 terhadap Pencatatan Perkawinan Beda Agama Menurut UU Adminduk: Penelitian - Sutisna, Enzellita Meliyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Interfaith marriage remains a complex legal issue in Indonesia, especially regarding its registration under population administration law. Despite constitutional guarantees of religious freedom, interfaith couples face legal uncertainty due to normative disharmony and legislative gaps. The issuance of Supreme Court Circular Letter (SEMA) No. 2 of 2023 prohibits judges from granting court decisions for registering interfaith marriages, previously seen as a legal alternative. This study employs a normative juridical method with descriptive-analytical specifications using library research. The findings show that SEMA No. 2 of 2023 restricts interpretations of Articles 35(a) and 36(1) of Law No. 24 of 2013, limiting administrative access and creating legal uncertainty. Although SEMA lacks formal legal hierarchy, its impact is significant. The persistence of interfaith marriages reflects a disconnect between constitutional rights and rigid legal norms. Thus, regulatory reform is urgently needed to align interfaith marriage registration with constitutional principles and administrative justice